Enhanced efficacy of immune checkpoint inhibitors by folate-targeted multifunctional drug through synergistic therapy inducing ferroptosis and immunogenic cell death in bladder cancer - Yibo Shi; Guangrui Fan; Enguang Yang; Yuanfeng Zhang; Hui Ding; Junqiang Tian; Liang Cheng; Hanzhang Wang; Tianzhi Hao; Baodui Wang; Zhiping Wang (Materials Today Bio)
Purpose: The research aims to elucidate the anti-tumor mechanism of the composite multifunctional folate-targeted drug DIFP-FA through sonodynamic therapy (SDT), chemodynamic therapy (CDT), and chemotherapy, as well as its potential to augment immune checkpoint blockade (ICB) therapy in bladder cancer (BC). Methods: DIFP-FA was synthesized via the W/O/W method. Its targeting efficacy was assessed using immunofluorescence and small animal imaging. Specific mechanisms were investigated through transcriptome sequencing and validation at both cellular and animal levels was conducted. BC patient-derived organoids (PDOs) and patient-derived tumor xenograft (PDX) models, derived from BC tissues resistant to cisplatin-gemcitabine and tislelizumab, were utilized to evaluate the efficacy of DIFP-FA in combination with SDT/CDT and chemotherapy. A humanized BC-PDX model was constructed to explore the synergistic effect of DIFP-FA with ICB therapy. Results: DIFP-FA, by incorporating doxorubicin and indocyanine green, leverages specific binding to folate receptors for precise targeting and efficient internalization into BC cells. DIFP-FA exhibits pH and ultrasound (US)-responsive cargo release properties, ensuring spatiotemporally controlled release. DIFP-FA induces reduced GPX4 and SLC7A11 expression and ferroptosis through the combination of SDT/CDT and chemotherapy. It also facilitates the transport and release of DAMPs, leading to immunogenic cell death (ICD). PDOs and PDX experiments demonstrated that DIFP-FA + US enhanced T lymphocyte infiltration in tumor tissues. Moreover, its combination with anti-PD-1 therapy effectively cleared immune-tolerant BC. Conclusions: DIFP-FA integrates SDT/CDT with chemotherapy to induce ferroptosis and ICD, efficiently eradicating tumors and activating the immune response, thereby enhancing the efficacy of ICB therapy.